New Orthogonal Small Set Kasami Code Sequence - Pramaita, I Nyoman; Diafari, I G.A.G.K.; Negara, DNKP; Dharma, Agus (Majalah Ilmiah Teknologi Elektro, 2015)
In this paper, the authors propose the design of a new orthogonal small set Kasami code sequence generated using combination of non-orthogonal m-sequence and small set Kasami code sequence. The authors demonstrate that the proposed code sequence has comparable auto-correlation function (ACF), cross- correlation function (CCF), peak cross-correlation values with that of the existing orthogonal small set Kasami code sequence. Though the proposed code sequence has less code sequence sets than that of the existing orthogonal small set Kasami code sequence, the proposed code sequence possesses one more numbers of members in each code sequence set. The members of the same code set of the proposed code sequence are orthogonal to each other.
Keywords: ACF, CCF, orthogonal code, spreading code